Classical Elements of Nature in Galway Kinnell’s The Book of Nightmares - Quirós-García , Elizabeth (Escuela de Ciencias Sociales y Humanidades, UNED, 2020)
The aim of this study is to analyze Kinnell’s The Book of Nightmares from an archetypal and mythological approach. While there have been different approaches to reading Kinnell’s book-length poem, their primary concern has been Kinnell’s work in relation to other poets of his generation rather than the analysis of the book-length poem as a unity in which archetypes and myth intersect, with a central focus that is: the classical elements (water, fire, air, and earth), as fundamental elements for the resolution of the binary oppositions life and death in the hero’s quest.. Therefore, for the purpose of this study, the Jungian archetypal approach will be assumed as well as Campbell’s mythical focus, considering that these perspectives are still a valuable means for the analysis of literary texts.